The disabilities of the arm, shoulder and hand (DASH) outcome questionnaire: longitudinal construct validity and measuring self-rated health change after surgery - Gummesson, Christina (BioMed Central, 2003)
BACKGROUND: The disabilities of the arm, shoulder and hand (DASH) questionnaire is a self-administered region-specific outcome instrument developed as a measure of self-rated upper-extremity disability and symptoms. The DASH consists mainly of a 30-item disability/symptom scale, scored 0 (no disability) to 100. The main purpose of this study was to assess the longitudinal construct validity of the DASH among patients undergoing surgery. The second purpose was to quantify self-rated treatment effectiveness after surgery. METHODS: The longitudinal construct validity of the DASH was evaluated in 109 patients having surgical treatment for a variety of upper-extremity conditions, by assessing preoperative-to-postoperative (6–21 months) change in DASH score and calculating the effect size and standardized response mean. The magnitude of score change was also analyzed in relation to patients' responses to an item regarding self-perceived change in the status of the arm after surgery. Performance of the DASH as a measure of treatment effectiveness was assessed after surgery for subacromial impingement and carpal tunnel syndrome by calculating the effect size and standardized response mean. RESULTS: Among the 109 patients, the mean (SD) DASH score preoperatively was 35 (22) and postoperatively 24 (23) and the mean score change was 15 (13). The effect size was 0.7 and the standardized response mean 1.2. The mean change (95% confidence interval) in DASH score for the patients reporting the status of the arm as "much better" or "much worse" after surgery was 19 (15–23) and for those reporting it as "somewhat better" or "somewhat worse" was 10 (7–14) (p = 0.01). In measuring effectiveness of arthroscopic acromioplasty the effect size was 0.9 and standardized response mean 0.5; for carpal tunnel surgery the effect size was 0.7 and standardized response mean 1.0. CONCLUSION: The DASH can detect and differentiate small and large changes of disability over time after surgery in patients with upper-extremity musculoskeletal disorders. A 10-point difference in mean DASH score may be considered as a minimal important change. The DASH can show treatment effectiveness after surgery for subacromial impingement and carpal tunnel syndrome. The effect size and standardized response mean may yield substantially differing results.